Peningkatan Kemampuan Bahasa Arab Melalui Program Magang - Nura Halid; Nurul Komariyah; Wirzani Ilyatun Nisa; Tadaam Maulana; Muhammad Haedar; Nasarudin (STAI AL-AMIN, 2025)
In making a significant contribution to the development of Arabic language learning methodology at the MI level through the development of an internship program model that is adapted to the characteristics of MI students, this research aims to analyze the effect of an internship program using interactive methods on increasing the ability to master Arabic vocabulary (mufradat) of grade 5 MI students. An-Najah. The research used a quasi-experimental approach with a pretest-posttest control group design. The research sample consisted of two classes, namely class VB as an experimental class (25 students) which was treated with interactive methods through an internship program and class VC as a control class (22 students) with conventional methods. Data collection is carried out through written tests and documentation. Data analysis used the Independent Sample T-Test with the help of SPSS version 20. The results showed significant differences between the two classes, with a significance value of 0.000 (<0.05). The average posttest score for the experimental class reached 83.85, while the control class was only 76.07. The research conclusion proves that the internship program with interactive methods is effective in increasing students' mastery of Arabic vocabulary through a student-centered learning approach, a variety of teaching methods, and a higher intensity of language practice.